Search for rapid and less expensive COVID-19 tests for lower middle-income countries-antigen based immunoassays remains a neglected tool - Ahmed, Sibtain (Journal of Ayub Medical College Abbottabad, 2021)
The expensive real time polymerase chain reaction (PCR) based tests are considered the current gold standard for COVID-19. Owing to the cost and scarce availability most countries have tested less than 5% of their population till now. In this situation antigen-based tests are less explored and neglected tool which can serve as the best alternative.